An in-vitro biomechanical comparison of annular ligament repair and reconstructions to restore radial head stability in anterior Monteggia fractures - Kirk Vannitamby, MD; Cole T. Fleet, MESc; Carlos Prada, MD, MSc, FEBHS; James A. Johnson, PhD; Graham J.W. King, MD, MSc, FRCSC (JSES International)
Background: Persistent or recurrent instability of the radial head (RH) remains a challenge in treating anterior Monteggia fractures despite anatomic restoration of the ulna. RH instability may be caused by the pull of the biceps muscle with rupture of the annular ligament and other soft tissue stabilizers of the proximal radius. Currently, the optimal method to stabilize the proximal radius is unknown. The purpose of this study was to compare annular ligament repair with three different ligament reconstructions in restoring anterior RH stability. Methods: Eight cadaveric upper extremities were mounted on an elbow simulator in 90 degrees of flexion with the forearm in neutral rotation. Simulated sequential biceps loading was applied in 10 N increments up to a maximum biceps load of 150 N to generate an anteriorly directed force to the RH. Testing was first conducted in the native state with all soft tissue intact, followed by sectioning the central interosseous membrane, the proximal interosseous membrane, and annular and quadrate ligaments. This was followed by the randomized evaluation of an annular ligament repair and three different ligament reconstructions, including a Bell Tawse reconstruction with triceps fascia (Bell Tawse reconstruction), a free tendon annular ligament reconstruction (Itadera reconstruction), and a free tendon anatomic annular ligament reconstruction (anatomic reconstruction). An optical tracking system was used to determine RH kinematics relative to the humerus. For all test states, the anterior translation of the RH relative to the capitellum was quantified as a measure of subluxation. Results: Sectioning the soft tissue stabilizers of the proximal radius produced a significant increase in anterior RH subluxation relative to the intact state (P < .001). The annular ligament repair was most effective at reducing anterior radial subluxation (P = 1.000). The Itadera reconstruction was the next most effective procedure at reducing anterior RH subluxation (P = 1.000) and was followed by the anatomic reconstruction (P = .192) and the Bell Tawse reconstructions (P = .015), respectively. Conclusion: Annular ligament repair was most effective in restoring normal RH stability; however, repair of this structure may not always be feasible as the tissues are often compromised by the injury and may not be reparable. The Itadera reconstruction was the most effective reconstruction technique at restoring RH stability and should be considered over alternative procedures when annular ligament repair is not feasible. These data also suggest that careful rehabilitation will be important postoperatively as residual RH instability can occur even with an anatomic reduction of the ulna and annular ligament repair or reconstruction.